2002
DOI: 10.1159/000063037
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the distribution of the telomeric sequence (T<sub>2</sub>AG<sub>3</sub>)<sub>n</sub> in rock wallabies, <i>Petrogale</i> (Marsupialia: Macropodidae), by fluorescence in situ hybridization

Abstract: The distribution of the conserved vertebrate telomeric sequence (T2AG3)n was examined by fluorescence in situ hybridization in the six Petrogale (rock wallabies) taxa of the lateralis complex. As expected, the (T2AG3)n sequence was located at the termini of all chromosomes in all taxa. However, the sequence was also present at several nontelomeric (viz., interstitial and centromeric) sites. The signals identified were associated with either anci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…The distribution of the telomeric sequence in these complements is consistent with ITSs as 'remnant' telomeres, i.e. it is invariably found at the site of rearrangements (Metcalfe et al, 1997(Metcalfe et al, , 1998(Metcalfe et al, , 2002(Metcalfe et al, , 2004. We have also examined three 2n = 22 ancestral macropodine karyotypes with little or no C-banding (Metcalfe et al, 1998(Metcalfe et al, , 2002.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…The distribution of the telomeric sequence in these complements is consistent with ITSs as 'remnant' telomeres, i.e. it is invariably found at the site of rearrangements (Metcalfe et al, 1997(Metcalfe et al, , 1998(Metcalfe et al, , 2002(Metcalfe et al, , 2004. We have also examined three 2n = 22 ancestral macropodine karyotypes with little or no C-banding (Metcalfe et al, 1998(Metcalfe et al, , 2002.…”
supporting
confidence: 63%
“…Three Petrogale chromosomal groups are recognised (Briscoe et al, 1982;Eldridge and Close, 1993), the lateralis/penicillata group (14 taxa), xanthopus group (three species) and brachyotis group (three species). All taxa of the lateralis/ penicillata and xanthopus groups were examined (this paper and Metcalfe et al, 1997Metcalfe et al, , 2002. Species from the brachyotis group (Petrogale) show extensive C-banding and are not included (Eldridge et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less frequently, tracts of this telomeric sequence can be detected at additional, non-telomeric locations, mainly at pericentric regions but also at interstitial sites, and the distribution of these internal telomeric signals (ITS) can vary among closely related species (Meyne et al 1990). ITS are generally considered to be relics of chromosome rearrangements (Meyne et al 1990, Metcalfe et al 2002, Nanda et al 2002 or to correspond to repetitive DNA rich in (T 2 AG 3 ) n sequences (Garagna et al 1997, Meyne et al 1990, Multani et al 2001, Pagnozzi et al 2000. In addition, molecular studies have suggested that some short internal telomeric repeats might have been originated by the repair of doublestranded breaks (Azzalin et al 2001, Faravelli et al 2002, Nergadze et al 2004.…”
mentioning
confidence: 99%